Prenatal Diagnosis and Intrapartum Management of Congenital Ranula - Ercan, Fedi; Sarikaya, Muslum; Toprak, Erzat; Findik, Sidika; Arbag, Hamdi; Acar, Ali (Zeitschrift für Geburtshilfe und Neonatologie, 2018)
A foetal sublingual cystic lesion was diagnosed by routine prenatal ultrasonography at 27 weeks of gestation. Foetal growth and amniotic fluid volume were normal. An ex utero intrapartum treatment (EXIT) procedure was performed, and the cyst was aspirated to allow breathing during planned Caesarean section. The cyst was totally excised when the newborn was 60 days old, and histopathological examination revealed a mucous cyst of the mouth floor.
Keywords: EXIT; lingual cyst; mucous cyst; oral cystic mass; prenatal diagnosis; ranula